Investigation of Water-Based Emulsions: Surface and Film-Forming Properties - Tigci, Yelda; Sarac, Ayfer (WILEY-V C H VERLAG GMBH, 2009)
In the present study, reaction components such as emulsifiers, emulsifier combinations, and initiators were used for the particle stabilization of water-borne vinyl acetate - butyl acrylate copolymer latexes. The effects of these parameters on the colloidal film-forming properties of the vinyl acetate-co-butyl acrylate latex colloidal, physicochemical, surface, and film forming properties were investigated, in particular the aspect of their surface coating applications.
Keywords: coatings; differential scanning calorimetry (DSC); films; transparency; water-soluble polymers; LATICES; LATEXES; Polymer Science